The Transformation of Social and Cultural Space in the Context of the Development of Transport Corridors - Gordeev, Sergey; Zyryanov, Sergey; Sitkovskiy, Arseniy (KnE Social Sciences, 2021)
This article discusses the methodology of analysis and forecasting of complex spatial systems, taking into account a lot of economic, social and cultural relationships that determine the specifics of the individual territories’ development. Particular attention is paid to the formation of specific zones on the basis of urban settlements along the path of transport corridors. In this regard, the authors introduce the concept of ”urban renewal centers” and give a definition. For its disclosure, the methodological part provides a list of related concepts, defines their boundaries and relationships, and also reveals the essence of the definitions of ‘transport corridor’ and ‘zone of transport corridor’. The authors proposed the use of vector estimates for the analysis of heterogeneous spatial systems of extended information volumes with the inclusion of sociological data and problem-oriented adaptation of visualization and processing of graphic data. As a result of a new, more detailed statement of the problem, we can go on to assess the prospects for the development of space for the complex and heterogeneous macro-regional and transboundary transport corridor Ural — Northern Kazakhstan. The study has fixed that development of urban renewal centers acts as a driver for the development of social and cultural spheres, as well as general economic conditions. The social and cultural transformation of urban settlements over time begins to determine their economic development potential. Such settlements are becoming centers of gravity in the labor market with many far-reaching development scenarios. Keywords: regional development, urban settlements, urban renewal, transport corridor, visualization